2015
DOI: 10.1111/jam.12856
|View full text |Cite
|
Sign up to set email alerts
|

Environmental assessment reveals the presence of MLB-1 human astrovirus in Uruguay

Abstract: This study highlights the benefits of an environmental surveillance to study emerging enteric viruses circulating in human societies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…Diversity of human AstV strains in water samples was studied by Sanger sequencing in previous studies 17 19 , 21 23 , except for one study applying next-generation sequencing 37 . Especially, diversities of MLB- and VA-AstVs in water samples were studied by only one 17 and two studies 17 , 18 , respectively. Therefore, only a limited number of genotypes/strains have been identified from water samples.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Diversity of human AstV strains in water samples was studied by Sanger sequencing in previous studies 17 19 , 21 23 , except for one study applying next-generation sequencing 37 . Especially, diversities of MLB- and VA-AstVs in water samples were studied by only one 17 and two studies 17 , 18 , respectively. Therefore, only a limited number of genotypes/strains have been identified from water samples.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous studies have investigated the presence of MLB-AstVs in water samples 17 , 18 . Each study identified one genotype, i.e., one study identified type 2 17 and the other identified type 1 18 . In the present study, multiple types of MLB-AstVs were identified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the emergence of MLB and VA HAstV genotypes have been also observed in sewage samples in Japan and Uruguay (Hata et al, 2015;Lizasoain et al, 2015). Sewage surveillance conducted in sewage samples from Uruguay also detected canine astrovirus clustering with strains detected previously in Italy (2008) and Brazil (2012) (Lizasoain et al, 2015b).…”
Section: Nr -Not Reportedmentioning
confidence: 72%